The association between peritraumatic distress, perceived stress, depression in pregnancy, and NR3C1 DNA methylation among Chinese pregnant women who experienced COVID-19 lockdown - Wei, Liqing; Ying, Xiaohong; Zhai, Mengxi; Li, Jiayu; Liu, Dan; Liu, Xin; Yu, Bin; Yan, Hong (Frontiers in Immunology, 2022)
Abstract Prenatal stress can affect pregnant women in an epigenetic way during the critical period of conception of their offspring. The study aims to investigate the relationship between peritraumatic distress, prenatal perceived stress, depression, and glucocorticoid receptor (NR3C1) DNA methylation among pregnant women who experienced COVID-19 lockdown in China. Study data were collected from thirty pregnant women in Wuhan and Huanggang, China. The Peritraumatic Distress Inventory was used to measure peritraumatic distress, the Edinburgh Postnatal Depression Scale was used to measure depressive symptoms, and the Perceived Stress Scale was used to measure perceived stress. DNA methylation in the exon 1F promoter region of the NR3C1 gene from the venous blood mononuclear cell genome was characterized by bisulphite sequencing. Correlation and linear regression were used for data analysis. The mean level of peritraumatic distress, perceived stress, and depression was 6.30 (SD=5.09), 6.50 (SD=5.41), and 6.60 (SD=4.85), respectively, with 23.33% of pregnant women being depressed. The mean NR3C1 methylation was 0.65 (SD=0.22). Prenatal depression was positively correlated with the degree of methylation in venous blood from the mother (r=0.59, p=0.001), and depression predicted methylation of NR3C1 gene at the CpG 8 site (β=0.05, p=0.03). No association was found between peritraumatic distress as well as perceived stress and methylation of NR3C1. The NR3C1 gene was susceptible to epigenetic modification of DNA methylation in the context of prenatal stress, and maternal depression was associated with increased NR3C1 methylation among women who experienced COVID-19 lockdown.